PROTEİN OKSİDASYONUNUN ANA MEKANİZMALARI - KAYALI, Refik; ÇAKATAY, Ufuk (Cerrahpaşa Medical Journal, 2014)
Background.- The oxidative modification of proteins by reactive species is implicated in the etiology or progression of a panoply of disorders and diseases. We summarize here the basic mechanisms of protein oxidation. Oxidation of proteins can lead to nitration of aromatic amino acid residues, oxidation of thiol groups, advanced oxidation protein products formation, and conversion of some amino acid residues to carbonyl derivatives. Oxidation can lead also to cleavage of polypeptide chain and to formation of cross-linked protein aggregates. Furthermore, functional groups of proteins can react with oxidation products of polyunsaturated fatty acids and with carbohydrate derivatives (glycation/glycoxidation) to produce inactive derivatives. Alterations in protein conformations can lead to increased aggregation, fragmentation, distortion of secondary and tertiary structure, susceptibility to proteolysis, and diminution of normal function.